2011
DOI: 10.1111/j.1462-5822.2011.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Echovirus 1 infection depends on biogenesis of novel multivesicular bodies

Abstract: SummaryNon-enveloped picornavirus echovirus 1 (EV1) clusters its receptor a2b1 integrin and causes their internalization and accumulation in a2b1 integrin enriched multivesicular bodies (a2-MVBs). Our results here show that these a2-MVBs are distinct from acidic late endosomes/lysosomes by several criteria: (i) live intra-endosomal pH measurements show that a2-MVBs are not acidic, (ii) they are not positive for the late endosomal marker LBPA or Dil-LDL internalized to lysosomes, and (iii) simultaneous stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 71 publications
7
56
1
Order By: Relevance
“…In CV-1 monkey kidney cells, virus moves rapidly to caveolin-positive structures within the cell (35); infection appears to involve cholesterol, caveolin, and dynamin, but perturbation of actin dynamics has no effect (35). In SAOS-␣2 cells, a human osteosarcoma cell line engineered to express VLA-2, EV1 first enters tubular-vesicular structures within the cytoplasm and ultimately appears in unusual multivesicular bodies, which accumu- late both caveolin and fluid-phase markers (32,36). Agents that interfere with macropinocytosis inhibit infection of SAOS-␣2 cells, either by preventing the internalization of virions (as seen with dominant negative CtBP1) or by preventing traffic to multivesicular bodies (as seen with EIPA) (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In CV-1 monkey kidney cells, virus moves rapidly to caveolin-positive structures within the cell (35); infection appears to involve cholesterol, caveolin, and dynamin, but perturbation of actin dynamics has no effect (35). In SAOS-␣2 cells, a human osteosarcoma cell line engineered to express VLA-2, EV1 first enters tubular-vesicular structures within the cytoplasm and ultimately appears in unusual multivesicular bodies, which accumu- late both caveolin and fluid-phase markers (32,36). Agents that interfere with macropinocytosis inhibit infection of SAOS-␣2 cells, either by preventing the internalization of virions (as seen with dominant negative CtBP1) or by preventing traffic to multivesicular bodies (as seen with EIPA) (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the last component of ESCRTs, the ATPase Vps4 (35), inhibits EV1 infection and EV1-MVB function (15). Therefore, we also wanted to examine the role of Vps4 in CVA9 infection.…”
Section: Effects Of Chemical Inhibitors Of Endocytosis On Cva9 Infectmentioning
confidence: 99%
“…In order to gain more accurate information of the pHs of the endosomes along the infectious CVA9 pathway, we performed an intraendosomal pH measurement assay (15,16). In the assay, a pH-stable AF-555 conjugate and a pH-sensitive fluorescein isothiocyanate (FITC) conjugate were introduced to forming CVA9-positive endosomes.…”
Section: Effects Of Chemical Inhibitors Of Endocytosis On Cva9 Infectmentioning
confidence: 99%
See 2 more Smart Citations